(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Currently, the focus of scientists is on research into the functioning of the language, which highlights the creative nature of word formation in the Russian language. One of the most noticeable manifestations of the author’s personality is word creation. Thanks to the author’s creativity, neologisms appear in speech, which carry an evaluative connotation of the realities of society. This article examines the phenomenon of word creation in the media space, the functioning of occasionalisms in media discourse.